To What Extend Does The Technology Disrupstion Affect The Sale Of Smes Banana Chips Products In Bandar Lampung? - Helmia Adita Fitra; Fran Sinatra (Journal of Science and Applicative Technology, 2019)
Small and Medium-Sized Enterprises (SMEs) in Indonesia, which is also known as Usaha Mikro Kecil dan Menengah (UMKM), play a significant role in determining national economic performance. Banana chips are the most well-known product in Bandar Lampung. As the provincial capital of Lampung Province, Bandar Lampung becomes the center of trade and services sector which is a vital sector of the downstream industry activity. One of the vital aspect in the downstream of Banana chips industry is selling. This study aims to examine the effect of disruptive technology on the sale of SMEs Banana Chips products in Bandar Lampung. This study conduct the quantitative approach by using multiple regression linear analysis. The findings show that the regression model of selling aspect has 0.594 in R2 value. It means that the regression model is able to represent the real condition about 59,4%. According to the model, among the 6 (six) predictor variables, the most-influencing variable on the sale of Banana chips products is online-based promotion.